The Impact of MSME Characteristics on Enhancing Voluntary Tax Compliance in Bayelsa State, Nigeria - Adigwe, Pretty Dennis (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
The impact of Micro, Small, and Medium-Sized Enterprises' (MSMEs') attributes on voluntary tax compliance in Bayelsa State, Nigeria, is examined in this study. Data was gathered from 171 MSME managers using a cross-sectional survey approach and standardized questionnaire; 140 valid replies resulted in an 81.9% response rate. Using regression analysis and Spearman's rank correlation, the study investigates the connections among sectoral differences, business size, ownership structure, profitability, and voluntary tax compliance. The results show that firm size and tax compliance have a substantial positive association (r = 0.821), suggesting that larger MSMEs are more likely to follow tax laws. Ownership structure and compliance show a moderate association (r = 0.600), indicating that companies with more owners are generally more financially accountable. On the other hand, sectoral differences have a poor connection (r = 0.218) with tax compliance, suggesting that compliance behaviour is not considerably impacted by the type of industry. Compliance and profitability have a positive correlation (r = 0.629), suggesting that more successful companies are better equipped to pay their taxes. In order to increase compliance rates, the report emphasizes the significance of creating a favourable tax administration regime for MSMEs through customized tax laws and instructional programs. In the end, these findings support economic stability and sustainable development by offering insightful information to stakeholders and policymakers looking forward to enhancing tax compliance and revenue collection in Nigeria's MSME sector.